Understanding Verbal Communication through Cross-Cultural and Quranic Contexts (Analysis on Da’i’s Response towards Globalisation Challenges) - Rahmi Rahmi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2013)
To face globalisation challenge,a da’i or Islamic preacher has to be aware of any change that occurs.Especially when he or she is intended to deliver Islamic messages to pluralist community that come from diffferent cultures, beliefs, opinions and needs.A common form of communication form that da’i can use in doing his or her mission is verbal communication. There are two kinds of perspectives that can be used as reference to know more about verbal communication knowledge. Firstly, it is can be investigated from Quranic context which implies about verbal communication strategies such as qaulan sadida, qaulan baligha, qaulan layyinan, qaulan ma’rufa, qaulan karima and qaulan maitsura. Secondly, concerning cross-cultural context, there are some issues that should be taken into account like communication styles like direct/indirect communication styles, elaborate/succinct communication styles, personal/contextual communication styles, instrumental/affective communication styles, gender differences in communication, pidgins and creoles and translation and interpretation.